Evolution of codon usage in Taenia saginata genomes and its impact on the host - Rahman, Siddiq Ur; Rehman, Hassan Ur; Rahman, Inayat Ur; Khan, Muazzam Ali; Rahim, Fazli; Ali, Hamid; Chen, Dekun; Ma, Wentao (Frontiers in Veterinary Science, 2023)
The beef tapeworm, also known as Taenia saginata, is a zoonotic tapeworm from the genus Taenia in the order Cyclophyllidea. Taenia saginata is a food-borne zoonotic parasite with a world-wide distribution. It poses serious health risks to the host and has a considerable negative socioeconomic impact. Previous studies have explained the population structure of T. saginata within the evolutionary time scale and adaptive evolution. However, it is still unknown how synonymous codons are used by T. saginata. Here, we used 90 T. saginata strains, applying the codon usage bias (CUB). Both base content and relative synonymous codon usage (RSCU) analysis revealed that AT-ended codons were more frequently used in the genome of T. saginata. Further low codon usage bias was observed from the effective number of codons (ENC) value. The neutrality plot analysis suggested the dominant factor of natural selection was involved in the structuring of CUB in T. saginata. Further analysis showed that T. saginata has adapted host specific codon usage patterns to sustain successful replication and transmission chains within hosts (Bos taurus and Homo sapiens). Generally, both natural selection and mutational pressure have an impact on the codon usage patterns of the protein-coding genes in T. saginata. This study is important because it characterized the codon usage pattern in the T. saginata genomes and provided the necessary data for a basic evolutionary study on them.